2014
DOI: 10.1016/j.socscimed.2014.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Advancing methodology in the study of HIV status disclosure: The importance of considering disclosure target and intent

Abstract: Advancing methodology in the study of HIV status disclosure: The importance of considering disclosure target and intent Dima, A.L.; Stutterheim, S.E.; Lyimo, R.; de Bruin, M. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 50 publications
(81 reference statements)
3
26
0
Order By: Relevance
“…A limitation of much disclosure research to date is the reliance on cross-sectional data to evaluate what is inherently a process that occurs over time [1]. A further limitation is the commonly used approach of operationalising disclosure as any versus no disclosure, or using sum scores to indicate the total number of persons to whom an individual has disclosed [15]. These approaches treat disclosure to different individuals as interchangeable events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of much disclosure research to date is the reliance on cross-sectional data to evaluate what is inherently a process that occurs over time [1]. A further limitation is the commonly used approach of operationalising disclosure as any versus no disclosure, or using sum scores to indicate the total number of persons to whom an individual has disclosed [15]. These approaches treat disclosure to different individuals as interchangeable events.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches treat disclosure to different individuals as interchangeable events. Rather, it has been argued that disclosure should be conceptualised as a multi-dimensional process consisting of clusters of disclosure events to different individuals, given that disclosure events are neither interchangeable nor independent [15,16]. Based on this idea, two recent studies have sought to extend the methodology of disclosure research using psychometric data reduction techniques in general adult HIV-positive populations [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…HIV disclosure is multi-dimensional, including attitudes toward and intention to disclosure and overt disclosing behavior (Dima, Stutterheim, Lyimo, & De Bruin, 2014; Rimal, Bose, Brown, Mkandawire, & Folda, 2009). Guided by the social cognitive theory (Bandura, 1999) and the theory of reasoned action (Fishbein & Ajzen, 1975; Ajzen, 2001), researchers have found that a number of social cognitive factors, particularly disclosure appraisal, may mediate the process from perceived stigma to HIV disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Disclosure of HIV status has been considered as an important component in HIV prevention and treatment due to its complex relationship with secondary prevention, healthcare access, treatment adherence, psychosocial adjustment, and family function [1]. However, disclosing HIV status to family members, particularly to children, is still a big challenge for people living with HIV (PLHIV) [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to demonstrating the importance of perceived consequences of disclosure (individual-level factors), recent studies have called for a multidimensional perspective to explore HIV disclosure [1]. The practice of disclosure is not just a single individual event [7], but is embedded in certain social relationships and a specific sociocultural context [8].…”
Section: Introductionmentioning
confidence: 99%